Studentsâ Need Analysis of English Reading Skills for Academic Purposes - Wahyono, Edi; Puspitasari, Dewi (Proceeding of International Conference on Teacher Training and Education, 2016)
The study explores studentsâ needs for English reading skills among students of English Language Studies. ItÂ also explores the difficulties in reading skill for academic purposes (English for research) faced by the students.Â The study is based on the two basic aspects of exploring language needs: Target Situation Analysis and PresentÂ Situation Analysis. The participants of the study are 13 graduate students of English Language Studies of PostGraduate Program in the third semester. Questionnaire is an instrument for data collection. Quantitative and qualitative data were analyzed descriptively. The study showed that most of students often have difficulties in reading English texts for academic purposes. They want to improve their comprehension level through EAP course and enable to improve their writing performance.